ANALISIS MANAJEMEN PROYEK DALAM USAHA TEH DARI KULIT BUAH NAGA - Jhohari Jhohari; Raihan Raihan; Gladys Christiani; Kevin Jonay Lie; Sahat Juliwan Tarihoran (Universitas 17 Agustus 1945, 2022)
Project management is the management used to plan, implement, and control, project activities and minimize risks related to project costs and time. This study aims to analyze project management in the TehGa business. The TehGa business is a business that sells tea bags mixed with premium quality dragon fruit peels. The methodology used by researchers in analyzing this business, namely descriptive qualitative research methods in the form of interviews, observation and quantitative. The results of this study, namely that the TehGa business is quite good at implementing 10 project management so that it helps expedite the flow of production in this business and directs the business on a more effective path in business.